Ambient Temperature Cycles Affect Daily Torpor and Hibernation Patterns in Malagasy Tenrecs - Dausmann, Kathrin H.; Levesque, Danielle L.; Wein, Jens; Nowack, Julia (Frontiers in Physiology, 2020)
HHibernation and daily torpor (heterothermy) allow endotherms to cope with demanding environmental conditions. The depth and duration of torpor bouts vary considerably between tropical and temperate climates, and tropical hibernators manage to cope with a wider spectrum of ambient temperature (Ta) regimes during heterothermy. As cycles in Ta can have profound effects on activity and torpor patterns as well as energy expenditure, we examined how these characteristics are affected by daily fluctuating versus constant Ta in a tropical hibernator, the lesser hedgehog tenrec (Echinops telfairi). Throughout the study, regardless of season, the tenrecs became torpid every day. In summer, E. telfairi used daily fluctuations in Ta to passively rewarm from daily torpor, which led to synchrony in the activity phases and torpor bouts between individuals and generally decreased energy expenditure. In contrast, animals housed at constant Ta showed considerable variation in timing and they had to invest more energy through endogenous heat production. During the hibernation season (winter) E. telfairi hibernated for several months in constant, as well as in fluctuating Ta and, as in summer, under fluctuating Ta arousals were much more uniform and showed less variation in timing compared to constant temperature regimes. The timing of torpor is not only important for its effective use, but synchronization of activity patterns could also be essential for social interactions, and successful foraging bouts. Our results highlight that Ta cycles can be an effective zeitgeber for activity and thermoregulatory rhythms throughout the year and that consideration should be given to the choice of temperature regime when studying heterothermy under laboratory conditions.